Intonation expressiveness of speech as a means of developing the emotional sphere of the future teacher - Пінська, О. Л. (Educational Dimension, 2011)
In the article essence and ways of development of intonation expressiveness of broadcasting opens up as to the mean of development of emotional sphere of future teacher.